MBTI를 활용한 융합형 교양교과목 연구 - 의사소통 능력, 협력적 자기조절, 인공지능 윤리의식의 변화를 중심으로 - 한정규(Jeong-Gyu Han); 홍준성(Jun-Sung Hong); 허혜연(Hye-Yeon Huh) (교양교육연구, 2025)
본 연구는 ‘MBTI 성격유형과 인공지능로봇 윤리’ 교양교과목이 대학생들의 의사소통 능력, 협력적 자기조절, 그리고 인공지능 윤리의식에 긍정적인 변화를 가져오는지 실증적으로 분석하고자 하였다. 연구 대상은 동의대학교에서 해당 교과목을 수강한 64명의 학생으로, 사전-사후 검사를 통해 변화를 검증하였다. 연구 결과, 의사소통 능력에서는 정보수집, 경청, 창의적 의사소통, 자기 드러내기 영역에서 유의미한 변화가 나타났으며, 특히 정보수집에서 가장 큰 변화를 보였다. 협력적 자기조절은 인지적, 행동적, 동기적 영역 모두에서 유의미한 증가를 보이며, 팀 활동과 시나리오 기반 학습이 협력적 자기조절 변화에 효과적임을 입증하였다. 인공지능 윤리의식은 안정성 및 신뢰성, 차별금지, 로봇의 권리에서 유의미한 향상을 보였으며, 그중 차별금지 영역에서 가장 큰 차이가 확인되었다. 반면, 고정관념적 사고 극복과 주도적 의사소통에서는 유의미한 변화가 나타나지 않아, 일부 성격 유형에 따른 의사소통 스타일의 차이가 원인일 가능성이 제기되었다. 본 연구는 교양교과목이 학생들의 의사소통과 협력적 문제해결 역량을 강화하고, 인공지능 기술의 윤리적 문제에 대한 민감성과 이해를 높이는 데 효과적임을 시사한다. 마지막으로 연구의 한계와 제언에 대해서 제시하였다. This study aimed to empirically analyse whether a liberal arts course on ‘MBTI personality types and AI robot ethics’ brings about positive changes in communication skills, cooperative self-regulation, and AI ethics awareness among university students. The subjects of the study were 64 students who took the course at Dong-A University, and the changes were verified through pre- and post-tests. The results of the study showed significant changes in communication skills in the areas of information gathering, listening, creative communication, and self-disclosure, with the largest change in information gathering. Collaborative self-regulation showed significant increases in cognitive, behavioural, and synchronous domains, demonstrating that team activities and scenario-based learning are effective in changing collaborative self-regulation. AI ethics awareness showed significant improvements in stability and reliability, anti-discrimination, and robot rights, with the largest difference in anti-discrimination. On the other hand, there were no significant changes in overcoming stereotypical thinking and assertive communication, raising the possibility that the differences in communication styles of some personality types may be responsible. This study suggests that liberal arts courses are effective in enhancing students' communication and collaborative problem-solving skills, as well as increasing their sensitivity and understanding of ethical issues in AI technology. Finally, limitations of the study and suggestions are presented. KCI Citation Count: 0